"Solidários nos demos as mãos": as associações mutualistas de trabalhadores na Parahyba do Norte (1881-1910) - Figueirêdo, Márcio Tiago Aprígio de (2016)
This study seeks to analyze the workers' associations in the Parahyba do Norte in the period between 1881 and 1930. These workers who lived through in the period the end of the 19th century and the first decades of the 20th century in the capital of Parahyba organized politically through mutual aid associations. From this analysis we seek to understand how the working class developed its class identity through relationships, through the associative culture present in the formation of this process. For this, in the introduction, we made a brief overview of the history of work, highlighting the need to study the associational life. At another time of the dissertation, we show how the economic policy and aesthetic exercised in the process of modernization of the capital has affected the living conditions of the working class, we also did the mapping of the associations founded in the period. Then we insert the associations in the scenario presented and observe its workings. Finally, we analyze the case of the Sociedade de Artistas e Operarios Mechanicos e Liberais, where we highlight the process of institutionalizing the relationship with the world of politics and the state. As theoretical foundation we used the referential of Social History English, we use various sources such as: book of minutes, government reports, almanacs and newspapers. The selected documentation allowed to understand how the associations effectively marked the life of the working class in the capital of Parahyba.